1996
DOI: 10.1007/bf00128682
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin production from the green alga Haematococcus pluvialis with different stress conditions

Abstract: Haematococcus pluvialis was induced to produce the astaxanthin pigment. A factorial design was carried out with three sodium acetate concentrations, 0.025, 0.05, 0.1 (gfl), and three NaCl concentrations (0.1, 0.2 and 0.4 %).The best conditions in algal culture for astaxanthin production were 0.2 % NaCI, 0.025 g/l sodium acetate and 0.05 g/1 sodium acetate, each a 3.0, 1.83 and 1.78 % of astaxanthin, production in base to total dry weight, respectively. The higher astaxanthin production by bioreactor was 18.6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 15 publications
(9 reference statements)
0
15
0
2
Order By: Relevance
“…Many yeasts have been described with an increase ability to produce carotenoids when they grow under unfavorable environment [22]. The enhancement of the accumulation of astaxanthin in cysts of Haematococcus pluvialis under salt stress conditions has been reported both in the dark and light by several workers [23][24][25][26][27][28][29][30][31]. The present study has pointed higher astaxanthin level in those leaves of the mangroves that are inundated for 10 to 12 hours by tidal waters (ambient water salinity during the period of investigation was 8.50 o / oo in the northern tip of Sagar Island and 27.23 o / oo in the southern tip of Sagar island) thus exposed to stress caused by aquatic salinity.…”
Section: /5mentioning
confidence: 99%
“…Many yeasts have been described with an increase ability to produce carotenoids when they grow under unfavorable environment [22]. The enhancement of the accumulation of astaxanthin in cysts of Haematococcus pluvialis under salt stress conditions has been reported both in the dark and light by several workers [23][24][25][26][27][28][29][30][31]. The present study has pointed higher astaxanthin level in those leaves of the mangroves that are inundated for 10 to 12 hours by tidal waters (ambient water salinity during the period of investigation was 8.50 o / oo in the northern tip of Sagar Island and 27.23 o / oo in the southern tip of Sagar island) thus exposed to stress caused by aquatic salinity.…”
Section: /5mentioning
confidence: 99%
“…Light intensity and nitrate were selected as effective factors from the FFD. Phosphate and acetate were included in CCD because they were known as induction factors for astaxanthin production [1, 4,10,14]. Central values of nitrate and phosphate were taken from the original concentration of MBBM while the acetate concentration was 0.2 g/L.…”
Section: Optimization Of Screened Factors For Astaxanthin Production mentioning
confidence: 99%
“…Of particular importance is depletion of the nutrient source in the medium [7,8]. Another report showed that N-deficiency [21] induced astaxanthin formation and C/N balance [12] in the medium determined the degree of carotene formation [4]. Phosphate starvation was reported previously to act as a trigger for the accumulation of astaxanthin [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trong khi đó, vi tảo lục Haematococcus pluvialis có khả năng tích lũy astaxanthin lên tới trên 4% sinh khối khô [10]. Vì vậy, hiện nay sản xuất astaxanthin từ loài vi tảo này đang được đặc biệt quan tâm nghiên cứu [2, 5,6,13,19]. Tuy nhiên, việc sản xuất astaxanthin hiệu quả từ loài vi tảo này còn gặp nhiều khó khăn bởi vì chúng có tốc độ sinh trưởng thấp và nhạy cảm với sự thay đổi của điều kiện nuôi cấy.…”
unclassified